Multiculturalism and Attitudes Toward Immigrants: The Impact of Perceived Cultural Distance. (July 2018) - Mahfud, Yara; Badea, Constantina; Verkuyten, Maykel; Reynolds, Kate
Multiculturalism can be construed in different ways with different effects on majority members' attitudes toward immigrant-origin groups. Thinking about why the broad goals of multiculturalism are important for society might reduce feelings of outgroup threat and less prejudicial attitudes. In contrast, thinking about how exactly these goals can be accomplished might evoke feelings of threat that lead to prejudice. The aim of this experimental research conducted in France and the Netherlands was to examine the effect of these two construals of multiculturalism of attitudes toward immigrants and whether these effects depend on perceived cultural distance. The findings show that a focus on why multiculturalism is important for society is more beneficial for attitudes toward immigrant-origin groups for people perceiving relatively high cultural distance. In contrast, a focus on how the goals of multiculturalism can be accomplished has a more detrimental effect on attitudes for people perceiving relatively low cultural distance.